Possible links between anomalies in the photoemission, optical and phonon spectra of high-Tc cuprates - Cojocaru, Sergiu (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2008)
The impressive number of anomalies discovered in high-Tc cuprates by different experimental probes continued to increase also in the last years, adding more to the complexity of the general picture. An intriguing feature of this picture is that the energy scales of these phenomena are very different, spreading from meV to eV. It might imply that the phenomena are actually unrelated. However, the fundamental concept of strong electron correlations, in which high and low energy scales are closely connected, could account in a natural way for the underlying physics and provide an appropriate framework for its description. In this context, the pioneering works of academician V.A. Moskalenko in the last decades constitute a major contribution to the development of this area of physics and our understanding of the emerging new materials. Being guided by this concept we present arguments for the existence of internal connections between apparently unrelated anomalies reported in photoemission, optical and neutron